Strategi Public Relations Program Paket Vaksin dan Peduli Pariwisata Untuk Meningkatkan Citra Positif Hotel The Square Surabaya - Farikha Rachmawati; Alma Andriyani; Tanisya Farah; Syalomita Nadia Putri; Daniel Anugerah; Nadifa Aprilia (Universitas Katolik Widya Karya Malang, 2023)
During the Covid-19 pandemic, almost all sectors were affected by the pandemic. Companies need strategies to be able to survive in the pandemic era. Public Relations is an important element in an institution and company, one of which is playing an important role in enhancing the company's positive image. This study aims to analyze and evaluate programs carried out by public relations at The Square Hotel in improving the company's good image in the pandemic era.Hotel The Square Surabaya is working with the Ministry of Tourism and Creative Economy (Kemenparekraf) to carry out a vaccine package program and also a care tourism program. The purpose of this study is to analyze the two programs being undertaken by Hotel The Square Surabaya. The method used in this research is to use a qualitative descriptive method. Data collection techniques were carried out by in-depth interviews.The results of the study show that the tourism care program and the vaccine package program are active strategies and apply stakeholder theory as a form of enhancing the company's positive image. Hotel The Square is also trying to carry out these activities in accordance with the program planning that has been done.